Development of Coldplay's compositional artistry: lyrical and inspirational qualities of 'fix you' / Ashrafiqal Areef Noor Azwad - Noor Azwad, Ashrafiqal Areef (2022)
This paper aims to investigate the development of Coldplay's Grammy Award winning artistic style. Writing lyrics is demanding qualities. It is not easy to combine lyrics and melody effectively like Coldplay. The purpose of this research is as a contribution of knowledge for other composers who enjoy high-quality lyrics to use them in their composition. The objectives of this research are to investigate the development of Coldplay's Grammy Award winning artistic style and to examine the musical and inspirational qualities of 'Fix You' by Coldplay.